FOSTERING RELIGIOUS HARMONY: NURTURING TOLERANCE IN ISLAMIC BOARDING SCHOOLS THROUGH KIAI'S EXEMPLARY, CURRICULUM, AND DAILY ACTIVITIES - Akmansyah, Muhammad; Azizah, Utami Yuliyanti; Nurnazli, Nurnazli (Universitas Islam Negeri Raden Intan Lampung, 2024)
Tolerance plays a pivotal role in fostering positive impacts within society, particularly in Indonesia where Pesantren (Islamic Boarding School), as the oldest educational institutions, shape the character of Santri (students) and instills the essence of tolerance. This article aims to describe and analyze how exemplary leadership by the Kiai (Islamic kiais), the curriculum taught, and the daily activities of students in fostering religious tolerance in Khalaf and Salaf Islamic Boarding Schools. The study was conducted as field research using qualitative descriptive methods, delving into Al-Mujatama’ al-Islami (khalafiyyah), and Arroudhotul Wahidah (salafiyyah) Islamic Boarding Schools. Data were gathered through interviews, observations, and documentation from kiais and student teaching staff. The systematic data analysis involved collection, reduction, display, and conclusion drawing, validated through source triangulation. The research results demonstrate that the kiais at both Islamic Boarding Schools exhibit exceptional leadership by promoting inclusivity and understanding through interactions with students from diverse backgrounds. They value dialogue, respect diverse opinions, and uphold tolerance. Al-Mujatama’ al-Islami Islamic Boarding School prioritizes religious education and practical skills to foster religious tolerance, while Arroudhotul Wahidah Islamic Boarding School excels in teaching Islamic Heritage Books, fosters tolerance, respect for diverse views, social consciousness, and discourse. Those Islamic Boarding Schools use structured schedules, group activities, and an all-encompassing educational strategy to foster respect, unity, and holistic growth among students. They cultivate individuals with diverse competencies and compassionate values, emphasizing how religious teachings influence attitudes toward tolerance and respect for religious diversity.